Rhinovirus Induction of the CXC Chemokine Epithelial-Neutrophil Activating Peptide-78 in Bronchial Epithelium - Donninger, Howard; Glashoff, Richard; Haitchi, Hans-Michael; Syce, James A.; Ghildyal, Reena; van Rensburg, Estrelita; Bardin, Philip G. (The Journal of infectious diseases, 2003)
Epithelial-neutrophil activating peptide-78 (ENA-78) induces neutrophil migration, an early response to viral infection. Rhinovirus serotype 16 (RV16) was used to infect primary bronchial epithelial cells and a cell line (BEAS-2B). Release of ENA-78 protein was measured by enzyme-linked immunosorbent assay, ENA-78 mRNA production was quantified by reverse-transcription polymerase chain reaction, and ENA-78 promoter activity was assessed by use of a promoter construct. After infection with RV16, ENA-78 protein and mRNA increased significantly, and RV16 induced 3-fold increases in ENA-78 gene transcription. Nasal ENA-78 measured in patients with asthma with and without RV infection was more elevated in patients with RV infection present. Our study demonstrates that ENA-78 is produced in bronchial epithelial cells in response to RV16 infection. With other chemokines, it may be an important initiator of neutrophil airway inflammation during RV common colds and thus may play a role in the development of virus-associated airway pathologies